Production and Characterization of Marble Glue - Asmhan Tomeh; Haneen Alama (My University, 2012)
Marble glue is an adhesive compound used to join parts of marble, granite and other stones in addition to fill holes and cavities that might exist. The objective of this project is to produce local marble glue according to local and international specifications and with competitive cost. This aim was blossomed from the non- existence of a local product to improve the Palestinian economy. The First step was started with execution a lot of trials to produce the local marble glue, followed by doing tests to determine the suitable sample. A layout for the plant was done; finally the cost of the plant was analyzed. The optimum sample which gives the best performance was composed from (38.835 % Polyester, 24.272% Pure CaCOs24.272% Cutting stone, and 12.6213% Talc); with 9.3015 (Mpa) average stress. The selling price of one kilogram of local marble glue is 19.998 NIS. The payback period of the project is 4 years with 12 years as project life.